IMPLEMENTASI CTL DALAM MATA KULIAH PRAKTIKUM METEOROLOGI- KLIMATOLOGI UNTUK MENINGKATKAN KOMPETENSI BEKERJA ILMIAH PADA MAHASISWA JURUSAN PENDIDIKAN GEOGRAFI UNNES (Forum Ilmu Sosial, 2014)
The results of self-evaluation Geography Unnes shows that theaverage duration of the study undergraduate Education Studies Geography is more than 4 years. The main causative factor lies in the preparation of the thesis that the time average of more than 12 months. Difficulty in writing his thesis student allegedly because they are not used to working scientific. The concept or practice of law that have been described in the classroom, it seems less able to develop the ability to work ilmiah.Penelitian is done in theDepartment of Geography at the subject of research students department of Geography. Types of research in the form of class action with some procedures or steps to be carried out. These stages are planning, action, observation / evaluation and ends with reflections. The results show the value than lab report results indicate that by using CTL there is an increasein student how scientific work. This is demonstrated by the increasing number of students who are able to work and make a map of rainfall at each cycle a cycle first, 56. 7 still confusion make maps of rainfall with nets Thiesen, only 43.3% were understand and be able to create a map of rainfall is in the second cycle, students are able to create and draw a map of rainfall with jarinng-nets models Thiesen increased to 83.3%. This result has met the completeness criteria that researchers set that is equal to 75% of the total sample / students. This shows that the models and approaches, students CTL capable and able to work scientifically in solving a particular problem in the lecture.